2004
DOI: 10.1093/imammb/21.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Lyapunov functions and global properties for SEIR and SEIS epidemic models

Abstract: Abstract. Explicit Lyapunov functions for SIR and SEIR compartmental epidemic models with nonlinear incidence of the form βI p S q for the case p ≤ 1 are constructed. Global stability of the models is thereby established.1. Introduction. It is traditionally postulated that the spread of an infection occurs according to the principle of mass action and associated with it the bilinear incidence rate. However, there are a variety of reasons why this standard bilinear incidence rate may require modification. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(124 citation statements)
references
References 1 publication
4
120
0
Order By: Relevance
“…Our global stability result for P * generalizes earlier results in [7,20]. The proof utilizes a global Lyapunov function motivated by the work in [13][14][15]. We have shown that introducing amelioration at stage k of the disease progression indeed may increase the basic reproduction number, and hence may have a negative effect on the disease control in the population.…”
Section: Proposition 62 the Constants B I As Defined In Equationsupporting
confidence: 63%
“…Our global stability result for P * generalizes earlier results in [7,20]. The proof utilizes a global Lyapunov function motivated by the work in [13][14][15]. We have shown that introducing amelioration at stage k of the disease progression indeed may increase the basic reproduction number, and hence may have a negative effect on the disease control in the population.…”
Section: Proposition 62 the Constants B I As Defined In Equationsupporting
confidence: 63%
“…Consequently, the function (4) is indeed a Lyapunov function [14]. This function is a generalization of the Lyapunov functions constructed in [10,8] for the case of the nonlinear incidence rate βI p S q .…”
Section: Proofmentioning
confidence: 96%
“…Hethcote (2000); Korobeinikov (2004)). Indeed, if the equation for the recovered population R is omitted (the constant population size assumption allows us to do so), the system (1.1) is equivalent to the SEIR model: x corresponds to susceptible population S, y to exposed population E, and ν to infective population I.…”
Section: Basic Modelmentioning
confidence: 99%
“…For the SEIR model there is a global Lyapunov function (Korobeinikov, 2004) which allows a straightforward investigating of global properties of the system (1.1) as well. The following theorem holds for the system.…”
Section: Basic Modelmentioning
confidence: 99%